(untitled) (Nepal Journal of Environmental Science, 2025)
Polyaniline (PANI)-coated traditional Nepali paper composites were synthesized via an in situ chemical oxidative polymerization process. Fourier Transform Infra-red Spectroscopy (FTIR), X-ray Diffraction (XRD), Optical Microscopy (OM) and Scanning Electron Microscopy (SEM) confirmed the PANI-coating. Additionally, the synthesized PANI powder (emeraldine salt) exhibited good antibacterial activity against Bacillus subtilis and Escherichia coli (zone of inhibition, ZOI: 0.5 cm each) and antifungal activity against Candida albicans (ZOI: 0.4 cm). In contrast, PANI-coated NK exhibited lower antimicrobial activity compared to powdered PANI. It was more effective against E. coli (ZOI: 0.3 cm) than against B. subtilis (ZOI: 0.2 cm). The antifungal activity against C. albicans was the lowest, with a ZOI of 0.1 cm. These findings demonstrate the potential of the composites for sustainable packaging applications with modest antimicrobial properties. Optimizing the polymerization process and material formulation could enhance their efficacy for eco-friendly active packaging systems.